A película do desejo: a subversão das identidades queers no cinema de Pedro Almodóvar - Nepomuceno, Margarete Almeida (2010)
This thesis discusses Pedro Almodóvar s idea of cinema as a producer of new meanings and discursive practices concerning the identities, gender and sexuality. The objective is to reformulate old normative concepts about the biological conditions of the body as decisive factors directly associated to gender and sexuality, as well as its non-historical, permanent and immutable condition that influenced the modern discourses. From the theory of Queer and the theory of performance it was opened a proper space to visualize and debate the brand-new identity patterns that involve new interpretations of gender and sexuality in a continuous and complex way, the criticism on hegemonic, monolithic, naturalizing and essential identities. The queer identities redefine the social natural patterns and their normalizing processes in the constitution of the subject, proposing an understanding of the analysis that aims to question the natural concepts about gender and indicate that the gender in itself is a result of such discussions. The idea of cinema developed by Pedro Almodóvar intends to call attention to the subversion of such identities and the creative process that visualizes these mutable subjectivities, the introspective new technologies and the building of contemporary materialities and desires.